THE NEW VISION OF THE EDUCATIONAL AND SCIENTIFIC PROGRAM BY SPECIALTY 091 «BIOLOGY AND BIOCHEMISTRY» - Babintseva, L. Yu.; Gorovenko, N. G.; Kyryk, D. L.; Solovyov, S. O.; Sukhanova, O. O.; Podolska, S. V.; Vyunytska, L. V. (Medical Informatics and Engineering, 2025)
Background. The study of the general properties and laws of the development of living organisms, the study of species diversity, as well as the chemical processes that occur inside living organisms – the knowledge provided by the sciences of biology and biochemistry contributes to solving the problems of humanity: the availability of a sufficient amount of food, the preservation of health population, preserving and improving the quality of the environment. Being in constant development and studying these important issues, modern biology and biochemistry are transdisciplinary fields of knowledge that require competitive, proactive, qualified specialists integrated into the European and global scientific and educational space. The new vision of training future specialists of the degree of Doctor of Philosophy in the specialty 091 “Biology and Biochemistry” (according to the international codification 0511 Biology and 0512 Biochemistry) in the branch of knowledge 09 “Biology” is presented. Material and methods. Among the features of modern biology, we highlight: the complexity and uncertainty of conditions involving the application of laws, theories and methods of natural sciences; studying the relationship between biological and social human development; systemic biomedicine; procedures and methods for studying the diagnosis and therapy of diseases and health assessment. The specified features and all areas of specialty related to the use of information and digital technologies, artificial intelligence. Results. Biology and biochemistry, along with other natural sciences, contribute to new discoveries that significantly increase the level of modern global health care: from personalized medicine to the biological foundations of human psychology, from the development of new bionic materials and devices to cellular engineering. Life is considered at different levels of its organization - from the molecule to the biosphere, and generalizations of biochemistry help to illuminate the evolution of the organic world and the question of the origin of life on Earth. Conclusion. The content of the proposed educational-scientific program in specialty 091 “Biology and Biochemistry” is aimed at training highly qualified and competitive specialists of the degree of Doctor of Philosophy, acquisition by them in the course of training of necessary theoretical knowledge and a complex of practical abilities, skills and competences to perform innovative research, also the implementation of the obtained results in practical health care.